SUBSTITUTION AND ADULTERATION - PAST AND PRESENT (AYUSHDHARA, 2017)
Ayurveda is a science where number of herbs were explained in classics for various diseases. Although this science has huge classical herbal data, there is a big drawback of the availability of those herbs. For this purpose the Acharyas explained about the concept of Abhava Pratinidhi Dravyas (Substitution of drug). The concept of substitution is available in the treatise of Bhavaprakasha and Yogaratnakara which explains Pratinidhi as; when there is unavailability of any particular drug during preparation of a compound, one should try to get another drug having similar potency in terms of Rasa, Guna, Veerya, and Vipaka.In present era, many pharmacies facing difficulties in getting genuinity of the raw herbal drug due to many reasons like deforestation, over exploitation, extinction of many species and incorrect identification of many plant species, which hampers the quality of the formulation which gives rise to the alternative use of substitution and adulteration of herbal raw drug. This paper is an attempt to understand the concept of substitution and adulteration in both classical as well as present era, which will enrich the current practices of Pratinidhi Dravyas (Substitute Drugs) in Ayurvedic science.